Resilience Meets the Water–Energy–Food Nexus: Mapping the Research Landscape - Hogeboom, Rick J.; Borsje, Bas W.; Deribe, Mekdelawit M.; van der Meer, Freek D.; Mehvar, Seyedabdolhossein; Meyer, Markus A.; Özerol, Gül; Hoekstra, Arjen Y.; Nelson, Andy D. (Frontiers in Environmental Science, 2021)
Resilience thinking is increasingly promoted to address some of the grand challenges of the 21st century: providing water, energy, and food to all, while staying within the limits of the Earth system that is undergoing (climate) change. Concurrently, a partially overlapping body of literature on the water-energy-food (WEF) nexus has emerged through the realization that water, energy, and food systems are intricately linked – and should therefore be understood and managed in conjunction. This paper reviews recent scientific publications at the intersection of both concepts in order to i) examine the status quo on resilience thinking as it is applied in WEF nexus studies; ii) map the research landscape along major research foci and conceptualizations; iii) and propose a research agenda of topics distilled from gaps in the current research landscape. We identify key conceptualizations of both resilience and nexus framings that are used across studies, as we observe pronounced differences regarding the nexus’ nature, scope, emphasis and level of integration, and resilience’s scope, type, methodological and thematic foci. Promising research avenues include i) improving the understanding of resilience in the WEF nexus across scales, sectors, domains, and disciplines; ii) developing tools and indicators to measure and assess resilience of WEF systems; iii) bridging the implementation gap brought about by (governing) complexity; iv) integrating or reconciling resilience and nexus thinking; v) and considering other development principles and frameworks towards solving WEF challenges beside and beyond resilience, including control, efficiency, sustainability, and equity.